2017
DOI: 10.1038/srep42038
|View full text |Cite
|
Sign up to set email alerts
|

Historical factors shaped species diversity and composition of Salix in eastern Asia

Abstract: Ambient energy, niche conservatism, historical climate stability and habitat heterogeneity hypothesis have been proposed to explain the broad-scale species diversity patterns and species compositions, while their relative importance have been controversial. Here, we assessed the relative contributions of contemporary climate, historical climate changes and habitat heterogeneity in shaping Salix species diversity and species composition in whole eastern Asia as well as mountains and lowlands using linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Our phylogenomic results support the hypothesis that most species of the HDM represent a monophyletic lineage within the Salix Chamaetia-Vetrix clade (Figs. 2, 3, S1, S2) (Fang & Zhao, 1981; Sun, 2002; Wang et al, 2017). The divergence time estimation suggests that the HDM clade diverged from the Eurasian clade at 23.9 Ma (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our phylogenomic results support the hypothesis that most species of the HDM represent a monophyletic lineage within the Salix Chamaetia-Vetrix clade (Figs. 2, 3, S1, S2) (Fang & Zhao, 1981; Sun, 2002; Wang et al, 2017). The divergence time estimation suggests that the HDM clade diverged from the Eurasian clade at 23.9 Ma (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the Himalaya-HDM and adjacent areas the earliest Salix fossils are reported from the early and middle Miocene (17–15 Ma) (Tao, 2000; Spicer et al, 2003; Hui et al 2011), and are younger than the fossil records of northeast China (Paleogene) (Tao, 2000), North America (Eocene) (Wolfe, 1987), and Europe (early Oligocene) (Collinson, 1992). Combined with the high species diversity and endemism of Salix in the Himalaya-HDM region, several researchers suggested that this area may have acted as a secondary diversification centre for the genus Salix (Fang & Zhao, 1981; Sun, 2002; Wang et al, 2017). However, this hypothesis was lacking any comprehensive molecular phylogenetic support.…”
Section: Introductionmentioning
confidence: 99%
“…org), including the Mean annual temperature (MAT) and Mean annual precipitation (MAP) during LGM which were reconstructed by MIROC-ESM model (Watanabe et al, 2011). Followed a previous study (Wang et al, 2017), we calculated the absolute values of the anomaly in the Mean annual temperature (MAT) and Mean annual precipitation (MAP) between the LGM and the present (Tano and Pano) to represent the historical climate change since the LGM (i.e., |MAT LGM -MAT present | and |MAP LGM -MAP present |). We also used normalized difference vegetation index (NDVI) (1-km 2 resolution; data comes from the Environment and Ecology Scientific Data Center of western China, National Natural Science Foundation, China http:// westdc.westgis.ac.cn) and elevation range (ELE) to represent the habitat heterogeneity.…”
Section: Environmental Datamentioning
confidence: 99%
“…In the Himalaya–HDM and adjacent areas, the earliest Salix fossils are reported from the early and middle Miocene (17–15 Ma) (Tao, 2000; Spicer et al, 2003; Hui et al, 2011), younger than the fossil records of Salix in northeast China (Paleogene) (Tao, 2000), North America (Eocene) (Wolfe, 1987), and Europe (early Oligocene) (Collinson, 1992). Combined with a high rate of species diversity and endemism of Salix in the Himalaya–HDM region, several researchers suggested that this area might have acted as a secondary diversification center for the genus Salix (Fang & Zhao, 1981; Sun, 2002; Wang et al, 2017). However, this hypothesis lacks any comprehensive molecular phylogenetic support.…”
Section: Introductionmentioning
confidence: 99%